Murky Water: Cyanobacteria, BMAA and ALS - F. Baugh Reginald (Journal of Neurological Research And Therapy, 2017)
Cyanobacteria have been implicated in the etiology of ALS for the past 50 years. The weakness of the theories of cyanobacteria or its neurotoxin, BMAA as the etiologic agent in ALS is the iniquitousness of cyanobacteria in the environment. In third world countries, clean water is far from commonplace, the exposure to cyanobacteria higher, yet the incidence of ALS is probably less than it is in developed countries. Even in the developed world, exposure to cyanobacteria is commonplace. Differences in the gut microbiome, possibly the presence of Proteobacteria, a protective agent against cyanobacteria toxins, may be important.
Keywords: Cyanobacteria